Core–shell nanostructures for better thermoelectrics. Issue 1 (30th November 2021) - Mulla, Rafiq; Dunnill, Charles W.
Abstract : The "core–shell" nanostructures can break the strongly coupled electronic and thermal parameters and help achieve high thermoelectric (TE) performance. Abstract : Substantial attempts have been made in recent decades to enhance the thermoelectric performance and find new materials. The inherent complexity and strong correlation between the electronic and thermal parameters of the materials pose serious challenges to enhance their thermoelectric performance. Recent studies on "core–shell" nanostructures and their nanocomposites have indicated that the new strategy of creating such structurally engineered materials can help in several ways to achieve high thermoelectric performances by breaking the strongly coupled electronic and thermal parameters. Furthermore, the dependence of the Seebeck coefficient and electrical conductivity on the carrier concentrations can be altered through the core–shell structure induced energy filtering effects. This review focuses on the experimental evidence and theoretical predictions in the context of core–shell nanostructures and their composite thermoelectric materials. It also highlights the fabrication processes and concepts used to produce these novel core–shell nanostructures.